2004
DOI: 10.1677/joe.0.1820203
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spatial and temporal expression patterns of bone morphogenetic protein family members in the rat uterus over the estrous cycle

Abstract: Recent studies have demonstrated that bone morphogenetic proteins (BMPs) play fundamental roles in female fertility. This is particularly evident in terms of the ovary. One major question that is just beginning to be addressed is the role of BMPs in the non-pregnant uterus. To help fill this gap, we used in situ hybridization to investigate the expression of BMP family members in the rat uterus over the estrous cycle. We found that the endometrial/uterine cycle is accompanied by the expression of several compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
191
3
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(217 citation statements)
references
References 93 publications
17
191
3
4
Order By: Relevance
“…There is evidence that both leptin and adiponectin receptors are expressed in the cumulus cells, and adiponectin receptors exhibit differential target gene expression profile in cumulus (CC) compared to granulosa cells (GC) [20,24]. One example of an interesting target gene is Bmp2, which has been implicated in follicular apoptosis and fetal germ cell differentiation in the ovary [6,10]. Adiponectin was found to upregulate the expression of Bmp2 in CCs [20], although whether the adiponectin Bmp2 interaction has a functional significance in vivo remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that both leptin and adiponectin receptors are expressed in the cumulus cells, and adiponectin receptors exhibit differential target gene expression profile in cumulus (CC) compared to granulosa cells (GC) [20,24]. One example of an interesting target gene is Bmp2, which has been implicated in follicular apoptosis and fetal germ cell differentiation in the ovary [6,10]. Adiponectin was found to upregulate the expression of Bmp2 in CCs [20], although whether the adiponectin Bmp2 interaction has a functional significance in vivo remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Follicular cells of secondary to antral follicles have also been shown to express other various BMP factors, such as BMP-2, BMP-3, BMP-4 and BMP-7, concomitantly with follistatin [30][31][32]. In vitro experiments using recombinant BMP-2, BMP-4 or BMP-7 have designated these BMP, as well as oocyte-derived BMP, as anti-luteinizing factors [19,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Except a solitary report by Erickson & Shimasaki (2003) on rat, no study could be found on BMPs in the CL. To the best of our knowledge, this is the first study on BMP6 in the CL of riverine buffalo.…”
Section: Discussionmentioning
confidence: 99%
“…In the ovary, investigations on BMPs are mainly studied in the follicle of rat (Erickson & Shimasaki, 2003), cow (Glister et al, 2010) and ewe (Juengel et al, 2006). Except a solitary report by Erickson & Shimasaki (2003) on rat, no study could be found on BMPs in the CL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation